The cognitive side of essential tremor: what are the therapeutic implications?. (November 2013) - Janicki, Sarah C.; Cosentino, Stephanie; Louis, Elan D.
While essential tremor (ET) has traditionally been categorized as a pure motor disease, cross-sectional and longitudinal studies of cognition in ET have demonstrated that these patients may have cognitive dysfunction. Recent epidemiological studies demonstrate an association between ET (particularly with onset after age 65) and increased risk for cognitive impairment and dementia. Although existing studies have generally conceptualized cognitive changes in ET as consistent with a 'frontosubcortical' or 'corticocerebellar' profile, results from these same studies suggest that cognitive impairment in ET may in fact be heterogeneous. Furthermore, the underlying mechanisms remain uncertain. Cognitive changes could be a byproduct of the cerebellar dysfunction of ET itself; alternately, they may be a feature of concomitant neurodegenerative diseases that have been associated in several studies with ET, including Alzheimer's disease, Parkinson's disease or progressive supranuclear palsy. While the study of cognitive dysfunction in ET has received research attention in recent years, the results of these studies have not been translated into the clinical domain and clinical practice. This review first summarizes the current literature on the potential relationships between ET and cognitive change. We then suggest areas of further clinical evaluation and treatment; these suggestions are directed at physicians caring for ET patients who may demonstrate or complain of cognitive impairment. As we discuss, clinicians should ideally screen ET patients for possible signs or symptoms of cognitive impairment in addition to assessing for psychiatric comorbidity and quality of life. These recommendations are in contrast to most current clinical practice, which does not routinely include such assessment among ET patients. To our knowledge, there have been no pharmacotherapeutic trials to date of any agent for cognitive change associated with ET. We believe that studies for this indication are now called for. Future efforts in this direction will also need to take into account the pathobiology of cognitive changes in ET, which itself is an area that is ripe for future investigations.